The Research of the Different Properties and Production Parameters having Influence on Deep-Drawing Sheets made of AlMg3 Alloy - Michna, Štefan; Hren, Iryna; Cais, Jaromír; Michnová, Lenka (Manufacturing Technology Journal, 2020)
This work was focused on the research of the different variability production deep-drawing sheets made of AlMg3 alloy which could influence on their deep-drawing properties e.g. non alloying elements Fe, Mn, heat treatment parameters and structure with aim to judge ascertained and analyzed properties of the sheets. The mechanical properties, mainly the highest elongation, and the other parameters (grain size, metallurgical purity), were measured due to they had had the main influence on the deep-drawing properties of the sheets made of AlMg3 alloy. For this research work had been obtained 5 deep-drawing sheets made of AlMg3 alloy with different production than chemical composition and heat treatment with the aim to realized ?complex analyze?, and to find up the best variant for production technology with the high deep-drawing properties.
Keywords: AlMg3 alloy; mechanical properties; elongation of material; deep-drawing; chemical composition; aluminum sheets; metallurgical purity; EDS analyses; grain size